2020
DOI: 10.1039/d0ra03817b
|View full text |Cite
|
Sign up to set email alerts
|

Concentration–composition-isotherm for the ammonia absorption process of zirconium phosphate

Abstract: Ammonia absorption process of zirconium phosphate has been studied by concentration–composition-isotherm, X-ray diffraction and thermogravimetry-mass spectrometry. The equilibrium plateau concentration appeared due to two phase coexistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…It has been reported that the interlayer distance of Zr(HPO 4 ) 2 ·H 2 O is similar to that of Zr(NH 4 PO 4 )(HPO 4 )·H 2 O 14 as shown in Table S1 . When ammonia is absorbed above 1.0 mol(NH 3 )/mol[Zr(HPO 4 ) 2 ·H 2 O], the interlayer distance changes, which probably caused a change in the ammonia absorption rate.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…It has been reported that the interlayer distance of Zr(HPO 4 ) 2 ·H 2 O is similar to that of Zr(NH 4 PO 4 )(HPO 4 )·H 2 O 14 as shown in Table S1 . When ammonia is absorbed above 1.0 mol(NH 3 )/mol[Zr(HPO 4 ) 2 ·H 2 O], the interlayer distance changes, which probably caused a change in the ammonia absorption rate.…”
Section: Resultsmentioning
confidence: 54%
“… (a) TG curves of Zr(NH 4 PO 4 ) 2 ·H 2 O (black line), 14 HTS473K (red line), and HTS673K (blue line) and (b,c) mass spectra at m / z 18 and 17 of desorption gas from Zr(NH 4 PO 4 ) 2 ·H 2 O (black line), 14 HTS473K (red line), and HTS673K (blue line) in a flowing Ar gas (300 cm 3 /min) with a heating rate of 5 K/min. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ammonia absorption process of zirconium phosphate has been studied using the concentration-composition-isotherm X-ray diffraction and thermogravimetry-mass spectrometry. It was clarified that the equilibrium plateau concentration appeared due to two-phase coexistence [ 59 ].…”
Section: Applications To Complexes and Compoundsmentioning
confidence: 99%
“…In our previous study, we have reported that α-zirconium phosphate (ZrP) , has a large ammonia absorption capacity compared with other proton-based materials such as zeolite, activated carbon (AC), and montmorillonite in the solid state in water . In recent years, Prussian blue (PB) type has been attracting attention as an ammonia adsorption material because of a large amount of ammonia adsorption. , Figure shows a comparison of the ammonia sorption of ZrP, Prussian blue analogues (PBAs), and conventional adsorbents in the low concentration of ammonia (under 10 ppm). ,, …”
Section: Introductionmentioning
confidence: 99%